PENGEMBANGAN SUMBER DAYA MANUSIA DALAM PENDIDIKAN: STRATEGI DAN IMPLIKASI UNTUK PEMBELAJARAN BERKUALITAS DI ERA GLOBAL - Suherman, Ujang; Victorynie, Irnie (As-Sulthan Journal of Education, 2025)
Human resource (HR) development is a key element in supporting the success of organizations, including educational institutions. However, the challenges of modernization and globalization require human resources who are not only technically competent, but also have strong moral and ethical values. This research aims to analyze the urgency of human resource development in the educational context, with a focus on improving the quality of teaching staff through training, learning innovation and effective leadership. The method used in this research is a literature review based on descriptive analysis to integrate theory and empirical findings related to human resource development in the education sector. The research results show that human resource development contributes to increasing teacher competence, preparing a competency-based curriculum, and implementing interactive learning methods. In addition, human resource development strengthens the role of religion in building the morality of teaching staff as an effort to fight the challenges of globalization and social change. The implications of this research emphasize the importance of planning strategies in human resource development programs that focus on continuous learning, innovation and collaboration. Thus, superior educational human resources can play an optimal role in improving the quality of education and building a young generation that is adaptive to global change.